EDUCATIONAL REFORMS IN SCHOOL EDUCATION AND THEIR IMPLICATIONS ON TEACHER EDUCATION (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Today, when it is globally acknowledged that lower education should be a right and higher education a privilege, at present we in India seem to be the grip of an overriding ideology which is governing our economy, society and culture. This is the ideology of marketisation, globalization and privatization. In order to meet the challenges of 21st century it becomes essential to bring about education reforms in India. There are various factors that mar the quality of education in India. Hence education should be socialized by bringing parity between education in schools belonging to private and public sectors. The present paper deals with reforms needed in school education and in teacher education institutions.